SEGMENTATION AND POSITIONING STRATEGY AT SDIT ROBBANI BANJARBARU - Siti Muzalifah; Muhammad Taqiyyuddin (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This study discusses the segmentation and positioning of educational services at SDIT Robbani Banjarbaru with the aim of knowing the implementation of the segmentation and positioning of Islamic education institutions. This research is a qualitative research with the main target of all school members who are involved in the marketing process. data collection using interview method. The results of this study indicate that: (1) SDIT Robbani Banjarbaru determines market segmentation by applying several segmentation approaches, namely: (a) demographic segmentation; (b) geographic segmentation; (c) psychographic segmentation; and (d) psychological segmentation. (2) SDIT Robbani Banjarbaru determines the positioning of its educational services in the academic and non-academic fields as well as by developing a